Effect of tamarind seed supplementation on growth performance and immunity in sex-reversed red tilapia’s diet (Oreochromis niloticus x O. mossambicus) - Wittawat Kaewpoy; Pornpimon Sangjun; Thuchapol Karaket; Pattareeya Ponza (Songklanakarin Journal of Science and Technology (SJST), 2021)
Tamarind seed, a by-product of tamarind paste production, contains usable nutrients in the kernel that could induce immunity in rats. This study aimed to determine the possibility of using tamarind kernel powder in red tilapia feed observing its effects on fish growth and immunity. A feeding trial was conducted using tilapia fingerlings fed with 1, 2.5 and 5% tamarind kernel powder (TKP) inclusion in feed for eight weeks. A control group were fed with diet without TKP. The average initial weights of the red tilapia ranged from 4.73 ± 0.10 to 4.87 ± 0.23 g/fish (P>0.05). Growth parameters were monitored during the feed trial. At the end of the trial, lysozyme activity was determined, and fish were subjected to a pathogen challenge by intraperitoneally injecting them with 1.6 x 108 CFU Aeromonas hydrophila. Results showed that the fish reached 29.07 ± 2.96 to 30.77 ± 2.05 g/fish sizes. The growth parameters (weight gain, ADG, FCR), blood counts, and hematocrit were not significantly different among the treatments (P>0.05). The lysozyme activity also showed no significant difference among the treatments (21- 28 units/milliliter). Fish mortality rate post-challenge with pathogen was not significantly different between control and treatments (P>0.05). The results showed that 5% tamarind kernel powder could be included as a binding agent in feed without affecting growth of tilapia during the nursery stage.